Music in American crime prevention and punishment - Hirsch, Lily E. (The University of Michigan Press, 2012)
Although the use of music for extramusical purposes has been a part of American culture for some time, the phenomenon remained largely unknown to the general public until revelations became widespread of startling military practices during the second Iraq War. In Music in American Crime Prevention and Punishment, Lily E. Hirsch explores the related terrain at the intersection of music and law, demonstrating the ways in which music has become a tool of law enforcement and justice through: police and community leaders’ use of classical music in crime deterrence and punishment; the use of rap lyrics as prosecutorial evidence; allegations of music as incitement to violence; and the role of music in U.S. prisons and in detention centers in Guantanamo, Iraq, and Afghanistan. In the course of her study, Hirsch asks several questions: How does the law treat music? When and why does music participate in the law? How does music influence the legal process? How does the legal process influence music? And how do these appropriations affect the Romantic ideals underlying our view of music?